EGFR Mutation as a Predictive Factor to Treatment Response ofTKI (Tyrosine Kinase Inhibitor) in Non-Small Cell Lung CancerStage 4: A Case Report - Rajabto, Wulyo; Angkasa, Yohana Kusuma (UI Scholars Hub, 2021)
Non-small cell lung cancer (NSCLC) typically presents in patients at an advanced stage, with a poor prognosis. The development of epidermal growth factor receptor (EGFR) – tyrosine kinase inhibitors (TKIs) and the systematic identification of EGFR mutations heralded the advent of targeted therapy in lung cancer, transforming the landscape of its treatment and prognosis. This is a case of 37 years-old female patient presented with metastatic bone disease secondary to pulmonary adenocarcinoma EGFR mutation positive which demonstrated a remarkable result to TKI.